Low-Density Lipoprotein Cholesterol Is Associated With Asymptomatic Sensorineural Hearing Loss in Patients With Systemic Lupus Erythematosus. Issue 6 (September 2016) - Ferrari, Ana Luisa V.; Calonga, L.; Lapa, Aline T.; Postal, Mariana; Sinicato, Nailu A.; Peliçari, Karina O.; Peres, Fernando A.; Valente, João Paulo; Soki, Marcelo; Appenzeller, Simone; Costallat, Lilian T.L.
Abstract : Objective: The aims of this study were to determine the frequency of asymptomatic sensorineural hearing loss (SNHL) in systemic lupus erythematosus (SLE) and to determine the association between SNHL and demographic, clinical, and laboratory features and cardiovascular risk factors. Methods: We conducted a cross-sectional study including consecutive female SLE patients. We performed audiometry and clinical and laboratory evaluation and determined cardiovascular risk factors in all patients. Statistical analysis included principal component analysis and logistic regression. Results: Eighty-nine women were included with mean age of 38.98 (SD, 7.77) years and mean disease duration of 10.29 (SD, 9.19) years. Asymptomatic SNHL was observed in 14 patients (16%). In logistic regression model, only low-density lipoprotein levels ( z = 2.64; P = 0.008) were associated with SNHL. Conclusions: We observed asymptomatic SNHL in 16% of SLE and an association with low-density lipoprotein levels suggesting atherosclerosis as a mechanism. Follow-up is needed to determine clinical implications.